2007
DOI: 10.1002/lt.21078
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent hepatocellular carcinoma after transplantation: Use of a pathological score on explanted livers to predict recurrence

Abstract: Milan and University of California at San Francisco (UCSF) criteria are used to select patients with hepatocellular carcinoma (HCC) for liver transplantation (LT). Recurrent HCC is a significant cause of death. There is no widely accepted pathological assessment strategy to predict recurrent HCC after transplantation. This study compares the pathology of patients meeting Milan and UCSF criteria and develops a pathological score and nomogram to assess the risk of recurrent HCC after transplantation. All explant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
126
2
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(132 citation statements)
references
References 20 publications
3
126
2
1
Order By: Relevance
“…However, these parameters have also been shown to be risk factors for tumor recurrence after primary OLT. [25][26][27][28] Therefore, patients who have tumors with such aggressive features would likely not benefit from OLT. Although the patients in this study are limited in number, we performed salvage OLT for six cases of recurrent HCC; none of them showed tumor recurrence to the present time (median follow up ϭ 24 months).…”
Section: Discussionmentioning
confidence: 99%
“…However, these parameters have also been shown to be risk factors for tumor recurrence after primary OLT. [25][26][27][28] Therefore, patients who have tumors with such aggressive features would likely not benefit from OLT. Although the patients in this study are limited in number, we performed salvage OLT for six cases of recurrent HCC; none of them showed tumor recurrence to the present time (median follow up ϭ 24 months).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, the MC remain the benchmark for any other prognostic criteria proposed for expanding the use of LT in patients with cirrhosis and HCC. 24,40,80 or >1000 ng/mL 12,18,51 Up-to-7 criteria met 21,26 Tumor size >3 cm, 36 12,30,33 Total tumor volume >28 cm 3 35 or >115 cm 3 24 Total tumor diameter >8 cm 12,42 Bilobar nodules 66 Multiple nodules 52,71,76 Nodule number >3 25,26 and 13 level 2b studies 27,30,33,34,36,39,40,42,47,48,[51][52][53] have confirmed the likelihood of detecting mVI, grade 3 tumors, and microsatellites as the tumor size and number increase beyond the MC. In patients with HCCs meeting the MC, mVI is detected at a rate of 10% to 15%, poorly differentiated tumors are detected at a rate of 13% to 33%, and microsatellites are detected at a rate of 7% to 28%.…”
Section: And Transplantation For Patients With Hcc Beyond Conventimentioning
confidence: 99%
“…26,48 Similar rates of histological markers of tumor aggressiveness and poor prognoses have been detected in patients slightly exceeding the MC, such as patients meeting the University of California San Francisco criteria, 52,84 even though a significant proportion of patients meeting the University of California San Francisco criteria are meeting the MC as well. 24,34,47,51 We identified 10 studies 16,18,26,28,47,48,51,52,63,72 reporting frequency data for mVI and tumor grades in patients meeting or not meeting the MC, and a meta-analysis of the odds ratios was performed accordingly (Fig. 3).…”
Section: And Transplantation For Patients With Hcc Beyond Conventimentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9][10][11] There is general agreement that clinical tumor characteristics are not ideal for predicting HCC recurrence after liver transplantation. The future winner of the contest to accurately predict HCC recurrence has not yet established a clear lead.…”
Section: Referencesmentioning
confidence: 99%